Odontoameloblastoma: A rare case with unusual presentation - Supreet Jain; Mathod C Shashikanth; Priyanka Agrawal; Rahul Singh (Wolters Kluwer Medknow Publications, 2016)
The odontoameloblastoma (OA), also known as ameloblastic odontoma, is a very rare odontogenic tumor that is similar to ameloblastoma in its locally aggressive behavior. OA includes odontogenic ectomesenchyme in addition to odontogenic epithelium that resembles an ameloblastoma both in structure and in behavior. Its clinical presentation, however, often mimics the more innocuous odontoma, and hence, the recognition of its aggressive nature is commonly only ascertained after its histopathologic diagnosis following enucleation. This paper presents a rare case of OA with unusual clinical and radiological features.